PENGARUH PRODUCT QUALITY DAN PRICE TERHADAP CUSTOMERS SATISFACTION PADA PENGGUNA HANDPHONE SAMSUNG DI KABUPATEN PASAMAN BARAT - Citra Suci Mantauv (Jurnal Apresiasi Ekonomi, 2016)
This study was intended to see how the effects of Product Quality and Price to Customers’ Satisfaction toward Samsung mobile phone users in West Pasaman. The population in this study was the samsung mobile phone users in West Pasaman with the sample size of 100, where sampling techniques using Convinience sampling techniques. From the results of this study, the variable Product Quality (X1) and Price (X2) significantly affects the Customers Satisfaction (Y) with a significant level of 0.000. The amount of influence Product Quality (X1) and Price (X2) on the Customers Satisfaction (Y) is 0.423 (R2 = 42.3). Keywords : Product Quality, Price, Customers’ Satisfaction